Isolation and Identification of Lactic Acid Bacteria from Peranakan Etawa h Crossbred Goat Milk - Widodo, Widodo (2014)
Lactic acid bacteria (LAB) are widely used in dairy fermentation. The aim of this study was to isolate and identify LAB from fresh milk of Peranakan Etawah crossbred goat in Yogyakarta, Indonesia. Fresh milk sample from three different farms were collected after milking and plated in to de Mann Rogosa Sharp e (MRS) agar sup plemented with 0.5% ox bile. A single colony was purified with a streaking method, followed by morphology and biochemical identification based on Gram staining, catalase test, motility, spore formation, and their growth on different carbon source s . Molecular identification was conducted based on the sequence of 16S rRNA gene. This study isolated four isolates from Peranakan Etawah crossbred goat milk. Based on 16S rRNA gene sequences, isolate M101 and M102 showed homology with Lactococcus garvieae , isolate M103 showed homology with Pediococcus pentosaceus , whereas isolate M104 showed homology with Lactobacillus paracasei subsp. Paracasei. Further experiments are being carried out to explore their ability and potential as starter culture for goat milk fermentation. Key Words: Goat milk, Lactic Acid Bacteria, Molecular identification.